1988
DOI: 10.3758/bf03214228
|View full text |Cite
|
Sign up to set email alerts
|

Attentional strategies for studying scientific texts

Abstract: Content-area novices develop rules as to what types of information (e.g., definitions, facts, equations) are important in texts (Dee-Lucas & Larkin, 1988).The study reported here indicates that these rules influence text learning. Experts and novices read and recalled science texts. Reading times and recall for different types of content were compared for the two groups. Results indicate that novices' importance rules function as part of novices' control schema during reading, influencing their attentional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Schematically, one might envision the structure of an argument as a set of shown that schema-consistent information leads to a more complete and coherent structure and that structure acts as a guide during retrieval (Bower, Black, & Turner, 1979;Bransford & Johnson, 1972;Dee-Lucas & Larkin, 1988;Dixon, Faries, & Gabrys, 1988;Mandler & Johnson, 1977;Meyer, Brandt, & Bluth, 1980;Meyer & Freedle, 1984;Staresina, Gray, & Davachi, 2009;Stein & Glenn, 1979). Researchers have found a similar pattern with arguments.…”
Section: Reading Argumentsmentioning
confidence: 99%
“…Schematically, one might envision the structure of an argument as a set of shown that schema-consistent information leads to a more complete and coherent structure and that structure acts as a guide during retrieval (Bower, Black, & Turner, 1979;Bransford & Johnson, 1972;Dee-Lucas & Larkin, 1988;Dixon, Faries, & Gabrys, 1988;Mandler & Johnson, 1977;Meyer, Brandt, & Bluth, 1980;Meyer & Freedle, 1984;Staresina, Gray, & Davachi, 2009;Stein & Glenn, 1979). Researchers have found a similar pattern with arguments.…”
Section: Reading Argumentsmentioning
confidence: 99%
“…Frequently, however, readers read expository text in an unfamiliar domain and therefore do not have specific content schemata to help them understand the text. Instead, readers have been shown to use surface aspects of the text, as well as specific linguistic devices to make inferences about what information is important, how specific propositions are related to other propositions, and so forth (e.g., Dee-Lucas & Larkin, 1988; Goldman & Durán, 1988; Kieras, 1985). These processes are critical to the construction of a coherent internal representation of the text and meaningful mental or situation models (e.g., Johnson-Laird, 1983; van Dijk & Kintsch, 1983).…”
mentioning
confidence: 99%
“…These information-type rules have important learning consequences. Previous %i research has found that novices spend more time on definitions than facts when reading physics passages, recall more definitions than facts afterwards, and include more definitions than facts In their summaries of physics texts (Dee-Lucas & Larkin, 1985Larkin, . 1986.…”
Section: Discussionmentioning
confidence: 99%